2020
DOI: 10.1038/s41529-020-0112-3
|View full text |Cite
|
Sign up to set email alerts
|

Real-time dissolution of a compositionally complex alloy using inline ICP and correlation with XPS

Abstract: The real-time dissolution of the single-phase compositionally complex alloy (CCA), Al1.5TiVCr, was studied using an inline inductively coupled plasma method. Compositionally complex alloys (CCAs), a term encompassing high entropy alloys (HEAs) or multi-principal element alloys (MPEAs), are -in general -noted for their inherently high corrosion resistance. In order to gain an insight into the dissolution of Al1.5TiVCr alloy, atomic emission spectroelectrochemistry was utilised in order to measure the ion dissol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…[ 86 ] However, in spite of the single‐phase structure of Al1.5TiVCr, selective dissolution of Al was reported at OCP and during anodic polarisation on 0.1 M NaCl. [ 87 ] This confirmed that Al 2 O 3 is less resilient to chloride than the oxide of Cr, Ti, and V. The dissolution rate of Al was found to decrease with increasing fractions of Cr (III), Ti(IV), and V(III) oxides in the passive film of AlTiVCr. Moreover, the presence of Ti was seen to inhibit the transpassive dissolution potential of V and Cr.…”
Section: Corrosion Case Studiesmentioning
confidence: 64%
See 3 more Smart Citations
“…[ 86 ] However, in spite of the single‐phase structure of Al1.5TiVCr, selective dissolution of Al was reported at OCP and during anodic polarisation on 0.1 M NaCl. [ 87 ] This confirmed that Al 2 O 3 is less resilient to chloride than the oxide of Cr, Ti, and V. The dissolution rate of Al was found to decrease with increasing fractions of Cr (III), Ti(IV), and V(III) oxides in the passive film of AlTiVCr. Moreover, the presence of Ti was seen to inhibit the transpassive dissolution potential of V and Cr.…”
Section: Corrosion Case Studiesmentioning
confidence: 64%
“…Apart from conventional alloys, most multi‐principal element alloys studied using ASEC are found to dissolve incongruently. [ 85–91 ] Evolution of dissolution rate of each alloying element from alloys is found to depend on applied potential, exposure duration, pH, and so on. For example, both pH and exposure duration influenced the dissolution ratios of υZnυAl$\frac{{{{{\upsilon}}_{Zn}}}}{{{{{\upsilon}}_{Al}}}}$ in Al‐Zn alloys, [ 72 ] υMgυSi$\frac{{{{{\upsilon}}_{Mg}}}}{{{{{\upsilon}}_{Si}}}}$ in Mg 2 Si.…”
Section: Dissolution and Fundamental Electrochemical Phenomenamentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it has to be understood that the term MPEAs includes both HEAs and MEAs, having composition of base elements in relatively larger proportion. Recently, a broader term compositionally complex alloys (CCA) has been coined to represent MPEAs [9].…”
Section: Introductionmentioning
confidence: 99%